Peran Manajemen Laba Memediasi Hubungan Antara CSR, GCG Dan Kinerja Perusahaan Keluarga - Iskandar Itan* (LPPM Universitas BSI, 2020)
ABSTRACTThis study looks into the mediating role of earning management on the relationship between corporate social responsibility (CSR), good corporate governance (GCG) and family-owned companies’ performance. This study uses the panel data approach, and 116 family-owned companies on Indonesia Stock Exchange are included as the sample for the period 2014 to 2018 and data were analysed using SPSS and Smart PLS 3.0 software. In this study, CSR is measured using index of ISO 26000, good corporate governance is measured by board size, independent commissioners, board of commissioners and audit quality, while firm performance is measured by return on asset (ROA), Tobin’s Q and earning per share (EPS). Meanwhile, earning management is measured using discretionary accruals (DA) with the modified Jones model. The results show that CSR and GCG can build positive impact on firm performance. The findings also show that earning management mediates the relationship between GCG and firm performance, while it failed to mediate the relationship between CSR and firm performance. Keywords: Corporate Social Responsibility, Corporate Governance, Earning Management, Firm Performance, Family-owned CompaniesABSTRACTThis study looks into the mediating role of earning management on the relationship between corporate social responsibility (CSR), good corporate governance (GCG) and family-owned companies’ performance. This study uses the panel data approach, and 116 family-owned companies on Indonesia Stock Exchange are included as the sample for the period 2014 to 2018 and data were analysed using SPSS and Smart PLS 3.0 software. In this study, CSR is measured using index of ISO 26000, good corporate governance is measured by board size, independent commissioners, board of commissioners and audit quality, while firm performance is measured by return on asset (ROA), Tobin’s Q and earning per share (EPS). Meanwhile, earning management is measured using discretionary accruals (DA) with the modified Jones model. The results show that CSR and GCG can build positive impact on firm performance. The findings also show that earning management mediates the relationship between GCG and firm performance, while it failed to mediate the relationship between CSR and firm performance. Keywords: Corporate Social Responsibility, Corporate Governance, Earning Management, Firm Performance, Family-owned Companies